2002
DOI: 10.1034/j.1399-3038.2002.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered eosinophil levels as a result of viral infection in asthma exacerbation in childhood

Abstract: Respiratory viral infection is known to be a significant cause of asthma exacerbation. Eosinophils have been considered to play an important role in the pathogenesis of virus-induced asthma exacerbations. To determine how often asthma exacerbation is caused by virus infections and to examine the relationship between eosinophilia and asthma episode, we investigated 64 children who experienced asthma attacks between October 1999 and March 2000. We used rapid enzyme immunoassays to detect antigens of respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…RV is a very simple plus-stranded virus with only viral genomic RNA in the virion. Previous report has suggested that dsRNA, generated from viral replication, can induce robust cellular responses (34). Here, we found that RV replication generated an enormous amount of RNA in the infected cells ( Figure 1A).…”
Section: Effects Of Dsrna-mediated Pathway In Rv-induced Gene Expressionsupporting
confidence: 64%
See 1 more Smart Citation
“…RV is a very simple plus-stranded virus with only viral genomic RNA in the virion. Previous report has suggested that dsRNA, generated from viral replication, can induce robust cellular responses (34). Here, we found that RV replication generated an enormous amount of RNA in the infected cells ( Figure 1A).…”
Section: Effects Of Dsrna-mediated Pathway In Rv-induced Gene Expressionsupporting
confidence: 64%
“…This supports the notion that very few copies of dsRNA are actually required to initiate PKR signaling. It is interesting to note that all the asthma-exacerbating viruses (such as RV, respiratory syncytial virus (34), and influenza) generate dsRNA in their life cycles. Therefore, it would be fruitful to continue the study of the role of dsRNA in airway inflammatory responses and asthma exacerbations.…”
Section: Genesmentioning
confidence: 99%
“…We found that 80% of asthmatic episodes in children were attributed to viral infections. This data are close to those reported by other researchers [40,41] who reported that respiratory viral infections precipitated acute exacerbations of asthma and were the most common reason for hospital admissions. Additionally, an Egyptian study by ElGamal et al [42] revealed that 71% of asthmatic episodes in children were attributed to viral infections.…”
Section: Discussionsupporting
confidence: 90%
“…MBP deposition has been observed in the bronchial tissue of patients with asthma [19], chronic urticaria, atopic dermatitis and immunoglobulin E-mediated cutaneous late phase reactions [20]. Furthermore, in the patients with bronchiolitis and bronchial asthma caused by RS virus infection, eosinophils and ECP were increased in the bronchoalveolar lavage fluids [21] and nasopharyngeal secretions [22,23,24]. Collectively, these in vitro and in vivo studies indicate that toxic eosinophil granule proteins, specifically MBP, may play an important role in the pathophysiology of asthma.…”
Section: Introductionmentioning
confidence: 99%